2023
DOI: 10.7717/peerj.15373
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of FBXO43 in hepatocellular carcinoma and its impact on tumor cell proliferation, migration and invasion

Abstract: Background The effects of FBXO43 on hepatocellular carcinoma (HCC) and its clinical significance have not yet been determined. This study aims to determine the clinical significance of FBXO43 in HCC and its impact on the biological functions of HCC cells. Methods Data from TCGA database were downloaded to investigate the expression of FBXO43 in HCC and its correlation with prognosis and immune infiltration. Immunohistochemical staining imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…Moreover, the expression of FBXO43 was found to be significantly increased in CRC patients with advanced T stage (III - VI), poorly differentiated tumors, and lymphatic metastasis. Previous studies have demonstrated the crucial involvement of FBXO43 in tumorigenesis, with upregulation observed in various malignancies such as HCC [ 14 , 15 ], breast cancer [ 10 ], and cholangiocarcinoma [ 11 ]. The activation of the PI3K/AKT/P27 signaling pathway via FBXO43 has been found to promote the progression of cholangiocarcinoma [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the expression of FBXO43 was found to be significantly increased in CRC patients with advanced T stage (III - VI), poorly differentiated tumors, and lymphatic metastasis. Previous studies have demonstrated the crucial involvement of FBXO43 in tumorigenesis, with upregulation observed in various malignancies such as HCC [ 14 , 15 ], breast cancer [ 10 ], and cholangiocarcinoma [ 11 ]. The activation of the PI3K/AKT/P27 signaling pathway via FBXO43 has been found to promote the progression of cholangiocarcinoma [ 11 ].…”
Section: Discussionmentioning
confidence: 99%